Le Vietnam au Kampuchéa : La stratégie de consolidation - Van Der Kroef, Justus (Études internationales, 1984)
Despite intense diplomatic activity between Vietnam and her Southeast Asian neighbors to reach a compromise in their conflict resulting from the Vietnamese invasion of Kampuchea, the Hanoi government shows every indication of seeking to secure a permanent military and political presence in Kampuchea. Also because of the devastation brought by four years of the Pol Pot regime (1975-79), and the extermination of much of the skilled and educated social strata in Kampuchea, the Hanoi government has sent some 40,000 Vietnamese party cadres, civil officials and professionally trained to direct public affairs. Additionally, some 100,000 Vietnamese farmer s have migrated into Kampuchea, settling in such key provinces as Kompong Speu, Takeo, and Kompong Cham. Additional tens of thousands of Vietnamese settlers have moved into cities and the disputed frontier area. As fighting between the Vietnamese and resistance groups affiliated with the ''Coalition Government of Democratic Kampuchea" intensifies, the Hanoi regime also has been expanding its logistical-military network. This includes the construction of a new road network — popularly called the "New Ho CM Minh Trail" — linking the Vietnamese cities of Hue and Vinh, across Southern Laos, with Northwestern Kampuchea. Additionally, during the early weeks of 1983, a twenty-five kilometres long trench, studded with landmines and bamboo spikes has been constructed just inside the Kampuchean frontier, running from the village of Kop beyond the village of Yeang Dangkum — a region of frequent guerilla clashes. Al on g with the 180,000 man force of regular military maintained by Vietnam in Kampuchea, these measures indicate intentions of Hanoi's consolidation of power. Especially in Southeast Asia fears have arisen of a permanent Vietnamese "colonization" process in Kampuchea.